Ecthyma gangrenosum secondary to MRSA in a young patient with chronic kidney disease. (2021) - Barry, Mazin; Alhijji, Ali; Alsubaie, Abdulaziz
Abstract: Ecthyma gangrenosum (EG) is a well-recognized dermatological condition classically associated with Pseudomonas aeruginosa infection, however, the association with other bacteria, especially gram positive, is rare. There are only a few reported cases of EG caused by staphylococcal infection. Here, we report a case in a young patient with chronic kidney disease (CKD) presenting with EG secondary to Methicillin Resistant Staphylococcus aureus .